A persuasive cognitive assistant system - Costa, Ângelo Gonçalo Araújo Silva (2016)
In this paper, we present a persuasive recommendation module to be included into the iGenda framework. iGenda is a cognitive assistant that helps care-receivers and caregivers in the management of their agendas. The proposed new module will allow the system to select and recommend to the users the action that potentially best suits to his/her interests. The multi-agent approach followed by the iGenda framework facilitates an easy integration of these new features.